LC-MS/MS를 이용한 수도권에 유통되는 친환경 농산물의 잔류농약 모니터링 및 안전성 평가 - 김종율(Jong-Yul Kim); 정유민(Youmin Jung); 오한슬(Hanseul Oh); 강성태(Sung-Tae Kang) (한국식품과학회지, 2015)
This survey was carried out in 2014 to estimate the pesticide residue levels in commercial environment-friendly agricultural products in Seoul metropolitan area. Pesticide residues in 27 commodities were examined and analyzed using LC-MS/MS, which can simultaneously detect up to 85 pesticides. A total of 441 samples were collected and analyzed. Among the detected samples, the residue levels in 1.2% of organic agricultural products and 2.2% of pesticide-free agricultural products exceeded the maximum residue limits (MRLs); hence, 1.8% of the total samples exceeded the MRLs. The safety of the detected pesticides was assessed by monitoring the acceptable daily intake level (ADI) and acceptable dietary exposure (ADE) to the pesticides via consumption of the commodities. ADI and ADE are found to be 0.07728-9.46530% and 0.00141-0.17210%, respectively, which means that the residual pesticides in the environmental-friendly agricultural products in Korea are below the safe limit and therefore, pose no potential public health risks. LC-MS/MS를 이용하여 동시분석 가능한 85종 농약을 대상으로 2014년 4-9월까지 수도권에서 유통되고 있는 친환경농산물의 잔류농약실태를 조사함으로써 그 안전성을 평가하고자 하였다. 수집된 농산물은 유기농산물 170건, 무농약농산물 271건으로 총 441건이었고, 이를 대분류별로 구분하면 채소류 389건, 과실류 10건, 곡류 14건, 콩류 4건, 버섯류가 24건이었다. 잔류농약 모니터링 결과 채소류와 버섯류에서 유기농산물은 170건 중 2건, 1.2%의 부적합률을, 무농약농산물은 271건 중 6건, 2.2%의 부적합률을 나타내어 총 441건의 시료 중 8건에서 정량 한계 이상의 잔류농약이 검출되어 1.8%의 부적합률을 나타내었다. 대분류별로는 채소류에서 389건 중 5건, 1.3%의 부적합률을 나타내었고, 버섯류에서 24건 중 3건, 11.1%의 부적합률을 나타내었으며, 품목별로는 얼갈이배추, 홍고추, 풋고추 각 1건, 상추 2건, 양송이 3건으로 나타났고, 나머지 과실류, 곡류, 콩류 총 28건에서는 잔류농약이 검출되지 않았다. 검출된 농약 성분은 dimethomorph, etofenprox, imidacloprid, clothianidin, thiamethoxam, methomyl, carbendazim 등 7종으로 검출량은 0.018-0.534 mg/kg 수준이었다. 검출된 농약은 1일 섭취 허용량에 의한 평가 방법을 이용하여 농약의 1일 섭취 수준(%ADI)과 1인 1일 섭취 수준(%ADE)을 확인하여 그 안전성을 평가하였다. 그 결과 %ADI는 0.07728-9.46530%, %ADE는 0.00141-0.17210% 수준으로 확인되어 농약이 검출된 농산물을 섭취하더라도 위해도는 매우 낮음을 알 수 있었다.